A case of erosive oral lichen planus in a child affected by β-Thalassemia after 5 years from bone marrow transplantation - Xueting Liu; Hong Yang (BMC Oral Health)
Abstract Oral lichen planus is a chronic immune-mediated inflammatory disease of the oral mucosa, primarily mediated by T lymphocytes, and is one of the most common oral mucosal diseases. However, it is relatively rare in children, with potential etiologies related to a history of immune-related conditions. Severe β-thalassemia is a serious hereditary blood disorder for which bone marrow transplantation remains the most effective treatment. One of the most dangerous complications of this procedure is graft-versus-host disease (GVHD). Autoimmune thyroid disease an organ-specific autoimmune disorder mediated by T cells, can be considered a specific form of GVHD.This paper presents a case of a male child who underwent bone marrow transplantation at the age of four due to severe β-thalassemia and developed oral lichen planus five years later. This case aims to explore the clinical manifestations, diagnosis, and treatment options of this disease, as well as the relationship between autoimmune thyroid disease and oral lichen planus in children, in order to provide a reference for the clinical diagnosis and treatment of similar conditions.